A highly enantio- and diastereoselective intramolecular Stetter reaction catalyzed by chiral triazolinylidene carbenes: catalyst and reaction development plus mechanistic studies - Read de Alaniz, Javier, author; Rovis, Tomislav, advisor; Finke, Richard G., committee member; Kennan, Alan J., committee member; Meersmann, Thomas, committee member; McNeil, Michael R., committee member (Colorado State University. Libraries, 2006)
A highly enantioselective intramolecular Stetter reaction has been developed with a new family of triazolinylidene carbenes. Subjection of α,α-disubstituted Michael acceptors to an asymmetric intramolecular Stetter reaction results in a highly enantioselective conjugate addition and a diastereoselective proton transfer. Available evidence suggests the diastereoselective protonation occurs via intramolecular delivery to the sterically more hindered face of the enolate. It was demonstrated that hexamethyldisilazane (HMDS) the conjugate acid of the base, the nature of catalyst, and concentration all affect the diastereoselectivity of the reaction. The substrate scope tolerates both aromatic and aliphatic aldehydes. A variety of electron rich and poor aromatic aldehydes afford the desired product in high enantiomeric excess and good yield. The nature of the Michael acceptor can include α,β-unsaturated esters, thioesters, ketones, amides, and aldehydes. Both five and six membered rings can be formed. This reaction has been subject of mechanistic study; deuterium and 13C kinetic isotope effects suggest that the rate-determining step is proton transfer when the intramolecular Stetter reaction is conducted in the presence of HMDS. The relative rate of the reaction is dependent on the nature of the aldehyde with electron deficient aldehydes undergoing faster reactions. Studies on the resting state of the triazolinylidene carbene in the presence and absence of HMDS were elucidated with the aide of 13C-labeled catalyst. Results from these studies have realized exogenous water or oxygen is detrimental to the active carbene species during the catalytic cycle. New reaction pathways available to in situ generated acyl anion equivalents have been discovered utilizing chiral triazolinylidene carbenes. The use of chiral triazolium-derived carbenes allowed for the conversion of α-haloaldehydes to esters and N-tosylimines to nitriles. Investigations have begun on the synthesis of a new family of chiral triazolinylidene-gold(I) complexes and their reactivity has been illustrated.
Keywords: organic chemistry